TEACHING ENGLISH PRONUNCIATION - Axmedova Aziza Abdulloyevna; Baxshilloyeva Feruza G'afurjonovna (Лучшие интеллектуальные исследования, 2023)
Abstract: English pronunciation is one of the significant parts of language teaching and learning because it affects learners communicative competence and performance. If learners do not have acceptable pronunciation this may decreases their self-confidence and restrict their social interactions. In this paper, the researcher defines the term pronunciation, explains the importance of pronunciation, declares the goals of English pronunciation, expresses techniques for teaching English pronunciation, elaborates the learner’s involvement in the pronunciation learning, represents the teacher’s involvement in the pronunciation instruction